Food consumption patterns, nutrient adequacy, and the food systems in Nigeria - Mekonnen, Daniel A.; Trijsburg, Laura; Achterbosch, Thom; Brouwer, Inge D.; Kennedy, Gina; Linderhof, Vincent; Ruben, Ruerd; Talsma, Elise F. (Springer, 2021)
Previous studies in Nigeria examined food and nutrition security mainly using anthropometric indicators, total calorie intake, or the household dietary diversity score (HDDS). However, recent evidence on nutrient and dietary gaps, especially from nationally representative surveys, is weak. This study contributes by examining factors influencing household mean nutrient adequacy and HDDS with focus on components of food systems in Nigeria. Based on the 2015/16 Nigeria General Household Survey, we found that fruits and animal source foods were the least consumed food groups. Yet, these food groups seem to be the main sources of difference in HDDS and were strongly associated with the mean probability of nutrient adequacy, given covariates. Among 11 nutrients under study, large shortfalls were observed in consumption of iron, vitamin B12, and riboflavin with probability of adequacy being 0.2 or below, followed by niacin, vitamin C, and zinc with corresponding probability of adequacy ranged between 0.48 and 0.58. Further, results suggested that mobile phone ownership by the household head, household’s access to electricity, improved sources of water for household consumption, and percent of the community with improved sanitation were strongly associated with HDDS. Heterogeneities in food groups and nutrient consumption and food system drivers are discussed.